Managing destinations : from theories to practices - Scott, Noel; Guerreiro, Manuela; Pinto, Patricia (Emerald Publishing Limited, 2024)
Tourism and hospitality managers around the world study tourism destination development and management. Topics such as land-use planning and strategy, transportation, law, and residents'attitudes to development, are important but have been under-studied until now. Managing Destinations: From Theories to Practices discusses both the theory and current issues of destination management and provides examples of current practice. The authors include papers submitted to the t-Forum conference (2020) on the theme of destination management. Topics covered include policy, planning and strategy, stakeholders, new markets, infrastructure, transport and research and knowledge transfer with contributions from countries as diverse as Brazil, Croatia, Italy, Portugal, Russia, Saudi Arabia, and Spain.
Includes index.
Keywords: Tourism -- Management.; Business & Economics -- Industries -- Hospitality, Travel & Tourism.; Hospitality, sports, leisure and tourism industries.; elektronické knihy; electronic books